2021
DOI: 10.1111/cobi.13754
|View full text |Cite
|
Sign up to set email alerts
|

Modeling scale up of anthropogenic impacts from individual pollinator behavior to pollination systems

Abstract: Article impact statement: Sublethal effects of pesticides and disease on pollinator foraging behavior threaten the stability of pollination systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…However, the treatments come at a cost: A recent study revealed Apis mellifera simultaneously treated with thymol and IMD performed worse on visual learning tests than bees exposed to either chemical alone (Colin et al., 2020). Thus, beyond the shortened life spans reported here, doubly exposed bees run the risk of less efficient pollination (Gegear et al., 2021). Some plants, however, benefit from offering NSMs that promote bee health: parasitized B. impatiens individuals forage more heavily on aucubin‐ and catalpol‐enriched Chelone glabra nectar than non‐infected individuals, increasing pollen receipt (Richardson et al., 2016).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the treatments come at a cost: A recent study revealed Apis mellifera simultaneously treated with thymol and IMD performed worse on visual learning tests than bees exposed to either chemical alone (Colin et al., 2020). Thus, beyond the shortened life spans reported here, doubly exposed bees run the risk of less efficient pollination (Gegear et al., 2021). Some plants, however, benefit from offering NSMs that promote bee health: parasitized B. impatiens individuals forage more heavily on aucubin‐ and catalpol‐enriched Chelone glabra nectar than non‐infected individuals, increasing pollen receipt (Richardson et al., 2016).…”
Section: Discussionmentioning
confidence: 70%
“…However, the treatments come at a cost: A recent study revealed Apis mellifera simultaneously treated with thymol and IMD performed worse on visual learning tests than bees exposed to either chemical alone (Colin et al, 2020). Thus, beyond the shortened life spans reported here, doubly exposed bees run the risk of less efficient pollination (Gegear et al, 2021).…”
Section: Potential For Systemic Pesticides To Disrupt Plant-pollinato...mentioning
confidence: 71%
“…We can hope that mark-recapture and genetic methods, while expensive and labor intensive [50] will continue to contribute important data on insect movement that could be incorporated into future iterations of our model. Another area of substantial uncertainty involves the pesticide records (and in particular the lack of data on insecticide treated seed), information on lethality, and how sublethal effects scale up to population, community and ecosystem consequences [51].…”
Section: Discussionmentioning
confidence: 99%
“…We can hope that mark-recapture and genetic methods, while expensive and labor intensive [58], will continue to contribute important data on insect movement that could be incorporated into future iterations of our model. Another area of substantial uncertainty involves the pesticide records (and in particular the lack of data on insecticide treated seed), information on lethality, and how sublethal effects scale up to population, community and ecosystem consequences [59]. For example, our maps show large differences in resistance among the urban land cover types, which largely reflects uncertainty in urban areas due to a lack of reporting.…”
Section: Assumptions and Future Directionsmentioning
confidence: 96%